2005
DOI: 10.1016/j.jcrs.2004.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser photorefractive keratectomy for hyperopia: 7.5-year follow-up

Abstract: In H-PRK, refractive stability achieved at 1 year was maintained up to 7.5 years with no evidence of hyperopic shift, diurnal fluctuation, or late regression. Peripheral corneal haze decreased with time but was still evident in a number of eyes at the last follow-up visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 35 publications
4
35
2
Order By: Relevance
“…The density of haze was lowered in 12-24 months. Peripheral haze stays persistent in eyes with higher dioptric correction [18][19][20][21][22][23][24][25][26]. In our study, we detected corneal haze in 6.57% of patients in group 1 and 31.57% of patients in group 2.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The density of haze was lowered in 12-24 months. Peripheral haze stays persistent in eyes with higher dioptric correction [18][19][20][21][22][23][24][25][26]. In our study, we detected corneal haze in 6.57% of patients in group 1 and 31.57% of patients in group 2.…”
Section: Discussionsupporting
confidence: 52%
“…A study by O'Brart et al, demonstrated that after 7.5 year follow-up period in eyes that received hyperopic PRK treatment, 65% had stable or increased BCVA levels. However 30% had one line vision loss, and 5% had two lines vision loss during this period [22]. Pacella et al, revealed that 92.8% of eyes had stable or increased BCVA levels, while 25% of eyes had 2 or more lines of vision loss on 7 th day of the hyperopic PRK treatment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is of particular relevance in the case of refractive surgery, which is directed at treating natural physiological variants rather than disease processes and especially important with the correction of hyperopia, as this condition not only tends to progress with age but becomes more symptomatic with developing presbyopia (17) . However, despite millions of 5 corrections having been performed world-wide over the past two decades, studies examining the long-term follow-up of hyperopic excimer laser procedures beyond 5 years are few with none beyond 10 years (18)(19) . The refractive and biomechanical stability of the cornea decades after such procedures, where the ablation and removal of tissue is in the corneal mid-periphery, nearer to the limbus than in myopic corrections, is unknown.…”
Section: Introductionmentioning
confidence: 99%